Mechanism of Rhodiola rosea–Euonymus alatus drug pair against rheumatoid arthritis: Network pharmacology and experimental validation - Qiu‐han Zheng; Lian‐yun Du; Ying Zhao; Zhong Zhang; Song‐lan Piao; Ying‐hang Wang; Zhi Pan (Immunity, Inflammation and Disease, 2023)
Abstract Purpose The present study aimed to explore the potential components and mechanisms of Rhodiola rosea–Euonymus alatus drug pair (TY) that ameliorate rheumatoid arthritis (RA). Methods The main active components, core targets, and important pathways of TY against RA were predicted by network pharmacology analysis. The binding activity between the main active components and the core targets was verified by the molecular docking technique. Collagen‐induced arthritis (CIA) rat model and tumor necrosis factor (TNF)‐α‐induced fibroblast‐like synovial cells in human RA (HFLS‐RA) model were established, respectively. The core targets were verified by cell counting kit‐8 assay, hematoxylin eosin, enzyme‐linked immunosorbent assay, real‐time polymerase chain reaction, and Western blot analysis, and the therapeutic effect of TY was evaluated. Results A total of 18 possible components and 34 core targets were obtained by network pharmacology, among which inflammatory response, phosphatidylinositide 3‐kinases (PI3K)‐AKT and MAPK pathways were involved in the therapeutic effect of TY on RA. The results of molecular docking showed that kaempferol and quercetin had high binding affinity to interleukin (IL)‐1β, IL‐6, matrix metalloproteinase (MMP)9, and TNF‐α. In vivo and in vitro experiments showed that TY dose‐dependently inhibited the proliferation of HFLS‐RA cells induced by TNF‐α, and significantly reduced the paw swelling and arthritis scores in CIA rats. At the same time, TY inhibited the production of inflammatory factors in CIA rat serum and TNF‐α‐induced HFLS‐RA cells. It also decreased the expression of PI3K, phospho‐protein kinase B, MMP1, MMP3, MMP9, and increased the protein and mRNA levels of tissue inhibitors of MMPs (TIMP)1 in synovial tissue. Conclusion TY can inhibit the PI3K/AKT signaling pathway and regulate the balance between MMPs and TIMP, thus playing a therapeutic role in RA.